THE INTERNALIZATION OF ISLAMIC VALUES DURING THE PRE-OPERATIONAL STAGE BASED ON THE PIAGET COGNITIVE PSYCHOLOGY - Arifa, Laily Nur (Proceeding of International Conference on Islamic Education (ICIED), 2022)
The learning of Islamic Study often receives critics as a tedious activity, inefficient, and tends to become a doctrine. On the other hand, the urge for religious values internalisation is in great demand as the moral crisis has emerged and affected our lives. Therefore, effective internalising Islamic values requires a more innovative and precise approach based on the students’ characteristics.   One of the suggested approaches for this purpose is the cognitive approach.   Therefore, this paper discusses the application of Islamic values in Islamic education learning through cognitive psychology. Since Piaget is considered an important figure in cognitive psychology, it is interesting to measure Piaget's theory of cognitive development in the internalization of Islamic values in PAI learning. According to Piaget, in terms of thinking, children are not a miniature version of adults but individuals who have different ways of thinking. The important implications of Piaget's theory in inculcating Islamic values at the pre-operational stage are instilling the value of honesty in early childhood by using the magic box method. Discipline values can be internalized in children in the pre-operational stage using the front and back method. Inculcating the value of cleanliness in pre-operational stage children can be done by doing a simple practice or video demonstration.